Simultaneous Saccharification and Fermentation of Sugar Beet Pulp for Efficient Bioethanol Production. (19th September 2016) - Berłowska, Joanna; Pielech-Przybylska, Katarzyna; Balcerek, Maria; Dziekońska-Kubczak, Urszula; Patelski, Piotr; Dziugan, Piotr; Kręgiel, Dorota
Abstract : Sugar beet pulp, a byproduct of sugar beet processing, can be used as a feedstock in second-generation ethanol production. The objective of this study was to investigate the effects of pretreatment, of the dosage of cellulase and hemicellulase enzyme preparations used, and of aeration on the release of fermentable sugars and ethanol yield during simultaneous saccharification and fermentation (SSF) of sugar beet pulp-based worts. Pressure-thermal pretreatment was applied to sugar beet pulp suspended in 2% w/w sulphuric acid solution at a ratio providing 12% dry matter. Enzymatic hydrolysis was conducted using Viscozyme and Ultraflo Max (Novozymes) enzyme preparations (0.015–0.02 mL/g dry matter). Two yeast strains were used for fermentation: Ethanol Red ( S. cerevisiae ) (1 g/L) and Pichia stipitis (0.5 g/L), applied sequentially. The results show that efficient simultaneous saccharification and fermentation of sugar beet pulp was achieved. A 6 h interval for enzymatic activation between the application of enzyme preparations and inoculation with Ethanol Red further improved the fermentation performance, with the highest ethanol concentration reaching 26.9 ± 1.2  g/L and 86.5 ± 2.1 % fermentation efficiency relative to the theoretical yield.